2022
DOI: 10.3390/challe13010007
|View full text |Cite
|
Sign up to set email alerts
|

Together Alone: Going Online during COVID-19 Is Changing Scientific Conferences

Abstract: The COVID-19 pandemic caused many scientific conferences to move online, posing a great challenge for scientific communication. This change offers potential advantages and disadvantages for inclusion, diversity, and scientific advancement. Here, we analyse participants’ experiences of the Why Study Mammographic Density? Conference to explore some of these issues and identify key points of contention between different stakeholders. We found that while increasing participant diversity is facilitated by online co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
10
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(10 citation statements)
references
References 29 publications
0
10
0
Order By: Relevance
“…COVID-19 also changed the scientific conference's operation. While online conferences might have advantages related to accessibility and costs, the loss of informal and spontaneous face-to-face interactions might lead some researchers to re-schedule the presentation of their research results (Bray et al, 2022). A meta-analysis conducted by Raynaud et al (2021) showed an 18 % decrease in the production of non-COVID-19 research, including agriculture, from 2019 to 2021.…”
Section: Discussionmentioning
confidence: 99%
“…COVID-19 also changed the scientific conference's operation. While online conferences might have advantages related to accessibility and costs, the loss of informal and spontaneous face-to-face interactions might lead some researchers to re-schedule the presentation of their research results (Bray et al, 2022). A meta-analysis conducted by Raynaud et al (2021) showed an 18 % decrease in the production of non-COVID-19 research, including agriculture, from 2019 to 2021.…”
Section: Discussionmentioning
confidence: 99%
“…Since February 2020, and the emergence of SARS-CoV-2, there has been both a dramatic change in the nature of scientific conferences, including chemistry education, and in the discussion of the fate of conferences among scientists. These changes have not diminished the sense of how important gathering to share scientific concepts is for the advancement of knowledge. Indeed, one important innovation associated with remote learning of chemistry has been finding ways to help students learn presentation skills related to chemistry in virtual environments. , Given this persistent interest in conferences, the convening of the 27th Biennial Conference on Chemical Education (BCCE) in-person this summer at Purdue University represented a much anticipated step toward familiar activities for many chemistry educators, with more than 1300 individuals registered for the conference.…”
mentioning
confidence: 99%
“…There have been observations that suggest the pandemic has likely changed the structure of scientific conferences for the better . Considering key factors such as cost and accessibility associated with virtual conferences suggests that what has been learned about holding online conferences will provide lasting value. Polls of scientists suggest that the prospect of permanence for at least some of these changes are widely viewed positively .…”
mentioning
confidence: 99%
See 2 more Smart Citations